A case report on mediastinal fixation to save physiology of mediastinum in a lung cancer patient. (2020) - Marzban-Rad, Saeid; Sattari, Parastesh; Marzban-Rad, Maryam; Azimi, Ghasem
Abstract: Introduction: The mediastinal space is confined from the top to the thorax inlet, at the bottom with the diaphragm. Presentation of case: A female with a right lung tumor with a history of chemotherapy, intubation, mediastinal fixation was performed on the affected side due to inadequate lung expansion, treatment-resistant fistula and intolerance of surgery to the pulmonary fistula. By fixing the mediastinal space on the affected side, right pleural space was drained. Conclusion: It is recommended that patients undergoing surgery for chronic empyema due to immunodeficiency and refractory infections, who do not tolerate surgery due to chronic pleural effusion and cavitation due to loculated Empyema develop thoracic surgery, fixation and continued treatment should be performed.